Refusal to Undergo PCR Testing for COVID-19, Tikrit 2021, a Cross-sectional Study - Aeed Hasan Alwan Alwan; Dr. Khattab Algbouri (American Journal of Biomedicine and Pharmacy, 2025)
Coronaviruses are a family of viruses that can cause illnesses such as the common cold, severe acute respiratory syndrome (SARS), and Middle East respiratory syndrome (MERS). A new type of coronavirus has been discovered after being identified as the cause of an outbreak that began in China in 2019. Local authorities have reported several suspected cases of COVID-19 and claim they have another differential diagnosis, which is helping the disease spread. Learn about the reasons for not taking a PCR test and find appropriate solutions. A descriptive cross-sectional study was conducted that included the opinions of (187) people from suspected cases who did not take a swab to diagnose the disease in the city of Tikrit for the period from 2/1/2021 to 5/30/2021. 62% of males, 29% in the 35-45 age group, 65% of urban residents, 43% have a fear of COVID-19, 26% have a fear of social stigma, followed by distrust of the institution (25% of the sample). Health education, increasing COVID-19 early screening centers, facilitating testing procedures, and finding alternative methods for swabbing. Continuously providing necessary materials and supplies, strengthening experienced and qualified human resources, and engaging with patients professionally are essential to restore confidence in healthcare institutions. Leveraging the results of social science research on COVID-19 to address social and psychological factors.